Prevalence of and factors associated with female sexual dysfunction among women using hormonal and non-hormonal contraception at the AGA Khan University Hospital Nairobi - Momin R. Butt; Valentino Lema; Abraham Mukaindo; Gulnaz Mohamoud; Jacob Shabani (AOSIS, 2019)
Background: Female sexual function (FSD) is a complex phenomenon. It integrates all body systems and is influenced by a variety of factors. Contraceptives have shown to have variable effects on FSD. In Kenya, the majority of women use hormonal contraception with high rates of discontinuation of use, attributed to related side effects such as weight loss and loss of libido. Aim: To determine the prevalence of and the factors affecting FSD among women using contraception in our setting. Setting: The study was carried out at the Aga Khan University Hospital, Nairobi, at various clinical sites. Methods: A cross-sectional study was conducted. Consecutive sampling of women of reproductive age using either hormonal or non-hormonal contraception was conducted. Two questionnaires were completed after obtaining informed consent. Independent associations of factors with the outcome variables were assessed using the chi-square test of association, and variables with a p 0.25 were used in the multivariate analysis. Factors associated with FSD were determined using binary logistic regression. Results: A total of 566 participants were included. The prevalence of FSD among those using hormonal and those using non-hormonal contraception was 51.5% and 29.6%, respectively (p 0.0001). We found that the factors associated with FSD were presence of chronic illness and use of chronic medication, being self-employed or unemployed, alcohol intake and history of miscarriage(s). Conclusion: There was a high prevalence of and a strong association between hormonal contraception and FSD. More studies on this topic in different settings are recommended to investigate the effect of each type of hormonal method on FSD.